(untitled) (Libellarium: journal for research in the field of information and related sciences, 2014)
This paper gives an outline of e-book business in Croatia, another European small language market, based on surveys of seven mayor e-book distributors conducted in February 2013 and February 2014. The research included collecting web catalogues by various e-book distributors and an interview with their representatives, asking them to confirm the established number of e-books. After data collection, researchers analysed and presented the exact number of unique e-book titles, publisher’s participation, types of e-book formats and their prices. The findings show that there are 1.654 unique e-book titles by 55 publishers currently available on seven main platforms, the most popular e-book format is EPUB (55%), while the average retail price is EUR 5,86.